PENINGKATAN KEMAMPUAN BERPIKIR KREATIF MATEMATIKA DENGAN PENDEKATAN KONSTRUKTIVISME - Magdalena Astri Lihu; Ryan Nizar Zulfikar; St. Muthmainnah Yusuf (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2021)
Mathematics learning is a teaching and learning process that is built by the teacher to develop students 'creative thinking skills that can improve students' thinking abilities, and can increase the ability to construct new knowledge as an effort to increase good mastery of mathematics material. This study aims to determine how to increase the ability to think creatively in mathematics with a constructivism approach in SMA Negeri 2 Kupang. The form of research used is Grounded Theory. Sources of data in this study are primary data and secondary data. There are three (3) data analysis techniques in this research, namely: data reduction, data presentation and conclusion drawing. The result of this research is an increase in mathematical creative thinking skills that get learning with a constructivism approach is higher than students who get conventional learning. The conclusion of this study is that there is an increase in the ability to think creatively in mathematics using the constructivism approach in class students at SMA Negeri 2 Kupang for the 2019/2020 academic year.